A facile modification of cation exchange resin by nano-sized goethite for enhanced Cr(VI) removal from water. Issue 12 (25th May 2022) - Wang, Siqiao; Yin, Weizhao; Bu, Huaitian; Zeng, Weilong; Li, Ping; Zheng, Xiangyu; Chiang, Penchi; Wu, Jinhua
ABSTRACT: A novel macroporous strong acidic cation exchange resin (D001) modified by nano-sized goethite (nFeOOH@D001) was fabricated by using a facile ethanol dispersion and impregnation method, and its efficiency for Cr(VI) removal was tested thereafter. Due to the dispersing effect of ethanol, FeOOH particles of 20–150 nm were coated on the D001 surfaces. The nFeOOH@D001 obtained a Cr(VI) removal efficiency and capacity of 80.2% and 7.4 mg/g respectively, 5 times and 8 times higher than that of the pristine D001. The Cr(VI) removal by nFeOOH@D001 followed the pseudo second-order kinetics and the Langmuir adsorption model. Column experiments also demonstrated that the nFeOOH@D001 exhibited a much better ability to remove Cr(VI) as compared to the D001. Additionally, the nFeOOH@D001 showed a potential for reusability and renewability. The adsorbed nFeOOH@D001 could be easily desorbed by 0.1 M acetic acid and a reuse efficiency of 92.7% could be maintained after 4 desorption–adsorption cycles. The used nFeOOH@D001 could be eluted by 0.1 M HCl to remove nFeOOH, and the renewed D001 could be recoated by nFeOOH and achieved a regeneration rate of 97.8% for Cr(VI) removal. The above results indicated that nano-sized goethite modification is a promising method to endow D001 with the ability to remove Cr(VI) from water. GRAPHICAL ABSTRACT: UF0001